Studi Kualitatif: Sumber Self-Efficacy Mobilisasi Pasien selama Perawatan di Rumah Sakit - Lina Erlina (Jurnal Kesehatan, 2019)
High self-efficacy increases a person's ability to achieve certain targets beyond their actual abilities. The role of self-efficacy on the mobilization ability patient's during hospitalization has been proven. However, the source of self-efficacy of the patient for mobilization is not yet known. This study aimed to know what sources of self-efficacy of the patient for mobilization during hospitalization. This study used a qualitative study in which the data collected through in-depth interviews with 10 patients in the internal medicine room. Eight themes were obtained: 1) Habits of mobilization before illness, 2) Effects that patients feel after mobilizing, 3) Availability of mobilization facilities, 4) The success of other patients mobilizes, 5) verbal expressions directly from other people, 6) Self-statement, 7) Patient's physical condition, 8) Patient's psychological condition. Obtained eight themes of the source self-efficacy of the patient for mobilization during hospitalization, but it is not yet known which source is the most important. Further research is needed to find out the role of mobilization self-efficacy sources towards increasing patient mobilization capabilities.